Private Hospitals in Sylhet City, Bangladesh: An Issue of Service Marketing - Uddin, Shamsu; Rahaman, Md. Mahbubur; Islam, Md. Mazharul (Asian Business Review, 2012)
Competitive environment among the industrial and service sector has also influenced the healthcare especially hospitals in private sector. There is a tremendous growth in private hospitals during the last three decades, due to inadequate healthcare facilities available at public hospitals to meet the near about 160 million people of Bangladesh. This factor had provided an opportunity for the private hospitals to fill this gap by providing better healthcare services to the patients that leads to patient’s satisfaction. This paper aimed to evaluate the service quality delivered by the private hospitals in Bangladesh based on patient’s perception.